Exploring a novel multifunctional agent to improve the dispersion of short aramid fiber in polymer matrix - K. Naskar; G. S. Shibulal (eXPRESS Polymer Letters, 2012)
Composites based on resorcinol formaldehyde latex (RFL) coated aramid short fiber and a polyolefin based thermoplastic elastomer, namely ethylene octene copolymer (EOC) were prepared by melt mixing technique. The effects of both fiber loading and its length on the mechanical and thermal characteristics of the composite under natural and sheared conditions were investigated. Both the low strain modulus and Young’s modulus were increased as a function of fiber loading and length. However, thermal stability of the composite was found to enhance with increase in fiber loading and was independent of fiber length. Due to poor interfacial interaction between the fiber and the matrix and the formation of fiber aggregation especially with 6 mm fiber at high loading, the elongation and toughness of the composite were found to decrease drastically. In order to solve this problem, a maleic anhydride adducted polybutadiene (MA-g-PB) was applied on the aramid fiber. The improvements in tensile strength, elongation at break, toughness to stiffness balance and a good quality of fiber dispersion especially with 6 mm short fiber were achieved. These results indicate the potential use of maleic anhydride adducted PB as a multifunctional interface modifying coupling agent for the aramid short fiber reinforced polymers to enhance the mechanical properties as well as fiber dispersion. FTIR analyses of the treated fiber and SEM analyses of the tensile fractured surfaces of the composite strongly support and explain these results.